The Integration of Islamic Economic Education in Developing Strategies for Sustainable Green Economic Transformation - I Nyoman Susipta; Gendut Budiwahyono; Ninik Dwi Atmini; Trinkul Kalita (International Forum of Researchers and Lecturers, 2024)
This study explores the integration of Islamic economic education with green economy principles, focusing on environmental stewardship and sustainability. Islamic education plays a pivotal role in fostering ecological awareness, integrating values such as khalifah (stewardship), maslahah (public welfare), and adl (justice), which align with green economic practices. The research investigates how these values are taught in Islamic educational settings, particularly in pesantren (Islamic boarding schools), and how they promote sustainable practices such as tree planting and livestock cultivation. The study highlights the role of Islamic financial mechanisms, such as zakat, waqf, and green financing, in supporting sustainable development and equitable resource distribution. It also examines how Islamic education instills eco-spiritual values and encourages sustainable behaviors among students. The findings suggest that Islamic universities emphasize ethical economic principles more than secular institutions, while secular institutions focus more on sustainability content. The study calls for a more integrated approach, where both ethical economic practices and sustainability principles are harmonized to equip students for leadership roles in a green economy. This integration is crucial for fostering responsible global citizens capable of addressing the intertwined challenges of economic growth and environmental preservation.